West Balkans Regular Economic Report no. 21, Spring 2022 : Steering Through Crises - World Bank (Washington, DC: World Bank, 2022)
Just as the economies of the Western Balkans were looking to growth recovery beyond the pandemic, a new set of challenges confronted the region. The economies of the Western Balkans saw a strong growth rebound in 2021 with a broad-based bounce back in economic activity. Financial stability remains sound due to support measures, but vigilance will be needed given exceptional uncertainty. There was especially strong growth in trade in 2021 as the region benefited from a recovery in global demand, but the conflict between Russia and Ukraine is expected to disrupt this trend. The economies of the Western Balkans now face an unusually uncertain outlook. An expanded conflict or prolonged war between Russia and Ukraine can trigger further disruptions to global trade and to energy and food prices. Refinancing risks can arise if external financial market conditions continue to tighten. Debt sustainability may become a concern if limited fiscal space is eroded by policy responses to higher energy and food prices. Risks of political polarization also remain.